Management of bladder cancer : a comprehensive text with clinical scenarios - Chang, Sam S. (Urologist); Konety, Badrinath R. (Springer, 2015)
This book provides a single, comprehensive reference source that incorporates the epidemiology, natural history, and the latest genetic and molecular biological findings of bladder cancer. This book discusses the diagnostic and staging evaluation of both non-muscle invasive and invasive bladder cancer and incorporates the new findings on markers for the diagnosis of bladder cancer. Risk stratified treatment of non-muscle invasive bladder cancer including various approaches to intravesical therapy are reviewed. Current guideline-based approaches to management and new data regarding diagnosis and prognostication of muscle invasive bladder cancer is analyzed and summarized. This book covers the application of chemotherapy for muscle invasive and advanced disease. The evidence-based application of multimodality therapy is highlighted. Gaps in current knowledge and important areas for clinical research are highlighted. Authored by experts in their respective fields, Management of Bladder Cancer: A Comprehensive Text with Clinical Scenarios serves as an easy and complete reference source for clinicians, researchers, individuals in training, allied health professionals and medical students in the fields of Urology, Medical Oncology, Radiation Oncology, Basic and Translational Science and Epidemiology. -- Source other than Library of Congress
Keywords: Bladder -- Cancer -- Handbooks; Interventional radiology; Medicine; Oncology; Urology; Oncology -- Handbooks; Urology -- Handbooks